Acute Corneal Hydrops Mimicking Infectious Keratitis as Initial Presentation of Keratoconus in a 10-Year-Old Child - Elise A. Slim; Elias F. Jarade; Bilal M. Charanek; Joelle S. Antoun; Adib I. Hemade; Sahar H. Awada; Henry W. Fakhoury; Carole G. Cherfan (Case Reports in Ophthalmological Medicine)
Purpose. To report a case of acute hydrops in a 10-year-old child with advanced keratoconus. Case Presentation. A ten-year-old boy diagnosed as having right eye (RE) infectious keratitis, not responding to antimicrobial therapy, was referred to our hospital. The diagnosis of infectious keratitis was established one month prior to his presentation following an episode of acute corneal whitening, pain, and drop in visual acuity. Topical fortified antibiotics followed by topical antiviral therapy were used with no improvement. Slit lamp examination showed significant corneal protrusion with edema surrounding a rupture in Descemet’s membrane in the RE. The diagnosis of acute corneal hydrops from advanced keratoconus was highly suspected and confirmed with corneal topography. Conclusion. Although a relatively rare disease at the age of 10 years, keratoconus can be rapidly progressive in the pediatric group. Keratoconus should always be considered in the differential diagnosis of progressive vision loss in this age group.